2018
DOI: 10.3389/fpls.2018.01544
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Imagery Analysis – Quantifying Appearance and Number of Sorghum Heads for Applications in Breeding and Agronomy

Abstract: Sorghum (Sorghum bicolor L. Moench) is a C4 tropical grass that plays an essential role in providing nutrition to humans and livestock, particularly in marginal rainfall environments. The timing of head development and the number of heads per unit area are key adaptation traits to consider in agronomy and breeding but are time consuming and labor intensive to measure. We propose a two-step machine-based image processing method to detect and count the number of heads from high-resolution images captured by unma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 30 publications
2
94
0
Order By: Relevance
“…With the development of deep learning models for point clouds [57,58], compared performance should be achieved from point clouds. Thought not directly comparable, due to the use of different accuracy metrics, the performance achieved here is generally in line to other previous studies that applied image data [34,37,38]. In Olsen et al [34] a 98% counting accuracy and median absolute error (MAE) between 1.88 and 2.66 were achieved for 18 sorghum varieties in the Midwestern United States.…”
Section: Panicle Counting Performance and Field-level Panicle Mappingsupporting
confidence: 87%
See 2 more Smart Citations
“…With the development of deep learning models for point clouds [57,58], compared performance should be achieved from point clouds. Thought not directly comparable, due to the use of different accuracy metrics, the performance achieved here is generally in line to other previous studies that applied image data [34,37,38]. In Olsen et al [34] a 98% counting accuracy and median absolute error (MAE) between 1.88 and 2.66 were achieved for 18 sorghum varieties in the Midwestern United States.…”
Section: Panicle Counting Performance and Field-level Panicle Mappingsupporting
confidence: 87%
“…The accuracy was based on a receiver operating characteristic (ROC) curve's area under the curve (AUC) metric-which is usually correlated with overall accuracy. Similarly performance was also reported in [37]. As highlighted before, this high accuracy came at the expense of significant feature engineering, which we circumvented in this study by applying a deep learning approach.…”
Section: Plot Nosupporting
confidence: 65%
See 1 more Smart Citation
“…State-of-the-art convolutional neural networks have been shown to perform well on a wide variety of phenotyping tasks. The applications of CNNs in plant phenotyping include image classification tasks such as plant species identification [1], stress identification [2], object detection arXiv:1910.01789v2 [cs.CV] 15 Oct 2019 and counting tasks such as panicle or spike detection [3,4,5,6], leaf counting [7], fruit detection [8]; as well as pixel-wise segmentation based tasks such as panicle segmentation [9,10] and crop-weed segmentation [11]. We refer the reader to [12] and [13] for a full treatment of deep learning in agriculture and plant phenotyping tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This order of annotated dataset is generally difficult to prepare for an individual or a research group. In the agricultural domain, it has been reported that sorghum head detection network can be trained with a dataset consisting of 52 images with an average of 400 objects per image 16 , while a crop stem detection network was trained starting from 822 images 17 . These case studies imply that the amount of data required in a specialized task may be less compared to a relatively generalized task such as ImageNet classification and COCO detection challenges.…”
Section: Introductionmentioning
confidence: 99%